A bidirectional scanning method for scanning transmission X‐ray microscopy. (21st January 2021) - Sun, Tianxiao; Zhang, Xiangzhi; Xu, Zijian; Wang, Yong; Guo, Zhi; Wang, Jian; Tai, Renzhong
Abstract : A bidirectional scanning method designed for scanning transmission X‐ray microscopy (STXM) with an S‐shaped moving track is presented. This work removes the limitations on bidirectional scanning caused by motor backlash and vibration, and significantly improves the efficiency of STXM experiments. Abstract : Scanning mode is a key factor for the comprehensive performance, including imaging efficiency, of scanning transmission X‐ray microscopy (STXM). Herein is presented a bidirectional scanning method designed for STXM with an S‐shaped moving track. In this method, artificially designed ramp waves are generated by a piezo‐stage controller to control the two‐dimensional scanning of the sample. The sample position information is measured using laser interferometric sensors and sent to a field‐programmable gate array (FPGA) board which also acquires the X‐ray signals simultaneously from the detector. Since the data recorded by the FPGA contain the real position of each scanned point, the influence of the backlash caused by the back‐turning movement on the STXM image can be eliminated. By employing an adapted post‐processing program, a re‐meshed high‐resolution STXM image can be obtained. This S‐track bidirectional scanning method in fly‐scan mode has been implemented on the STXM endstation at the Shanghai Synchrotron Radiation Facility (SSRF), and successfully resolved the ∼30 nm interval between the innermost strips of a Siemens star. This work removes the limitation on bidirectional scanning caused by motor backlash and vibration, and significantly improves the efficiency of STXM experiments.